2016
DOI: 10.1586/17474124.2016.1166951
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric liver transplantation: a North American perspective

Abstract: Liver transplantation (LT) is an important component in the therapeutic armamentarium of managing end-stage liver disease. In North American children, biliary atresia remains the most common indication for LT compared to hepatitis C in adults, while hepatoblastoma is the most common liver tumor requiring LT, versus Hepatocellular carcinoma in adults. Rejection, lymphoproliferative disease, renal insufficiency, metabolic syndrome, recurrent disease, 'de novo' autoimmune hepatitis and malignancy require careful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Patients receiving sirolimus were not included in these studies. These are consistent with previously published definitions of “maintenance” immune suppression for pediatric liver transplantation where the goal is often low dose (3‐10 mg prednisone) or cessation of steroid with calcineurin inhibitor monotherapy . The consortium agreed on the following thresholds: tacrolimus trough levels of <8 ng/mL for two consecutive readings or cyclosporine levels of <100 ng/mL for two consecutive readings. prednisone dose equivalent to <2 mg/kg/d or total cumulative dose of <20 mg/d for those >10 kg. …”
Section: Outcomesupporting
confidence: 81%
See 3 more Smart Citations
“…Patients receiving sirolimus were not included in these studies. These are consistent with previously published definitions of “maintenance” immune suppression for pediatric liver transplantation where the goal is often low dose (3‐10 mg prednisone) or cessation of steroid with calcineurin inhibitor monotherapy . The consortium agreed on the following thresholds: tacrolimus trough levels of <8 ng/mL for two consecutive readings or cyclosporine levels of <100 ng/mL for two consecutive readings. prednisone dose equivalent to <2 mg/kg/d or total cumulative dose of <20 mg/d for those >10 kg. …”
Section: Outcomesupporting
confidence: 81%
“…There are concerns that live viral vaccines could precipitate rejection . Literature review found only one reported case of acute rejection temporally associated with live vaccination, which occurred 21 days after measles‐containing vaccine in a liver transplant recipient (Table ).…”
Section: Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…Liver transplantation (LT) is a life saving treatment for children with decompensated chronic liver disease, unresectable tumors, fulminant liver failure, and in some instances also for inherited metabolic conditions (1)(2). Stepwise innovations in surgical techniques, living donor (LD) LT, as well as the use of reduced size or split grafts have emerged in the last decades, increasing graft utilization for pediatric recipients.…”
Section: Introductionmentioning
confidence: 99%